Helium bubble facetation in tungsten thin films. (November 2022) - Bergstrom, Zachary J.; Perez, Danny; El-Atwani, Osman
Graphical abstract: Abstract: Helium bubbles naturally form in irradiated materials and their shape can potentially have a significant impact on mechanical property degradation. Experimental observations of helium bubble facetation are compared to theoretical equilibrium shapes based on surface energy, known as Wulff constructions, obtained from density functional theory (DFT). The shape and orientation of implanted He bubbles match very well with those determined from a thermodynamic analysis, with discrepancies attributed to kinetic factors, such as the anisotropic absorption of mobile helium-vacancy clusters and increased barrier to nucleate facets from the density of helium contained within the bubbles.